Assessing safety of journalism practice in Ghana: Key stakeholders’ perspectives - Theodora Dame Adjin-Tettey; Sulemana Braimah (Cogent Social Sciences)
This study sought to use the self-reporting method of survey as well as key informant interviews to investigate the depth and spread of the problem. A total of 115 respondents took part in the survey. Additionally, eight interviews were conducted with key stakeholders. The study found that the most common infraction was verbal abuse. Colleagues, police, political fanatics, politicians, security operatives and government officials, were among the top perpetrators of safety violations against journalists. A sizeable portion (albeit fewer) were dissatisfied with their workplace safety provisions and minimal confidence in the concern of their employers for their well-being. About half of respondents indicated their media organisations did not make provisions for safety gear for covering potentially dangerous beats. Many of the respondents thought that the posture, attitude and actions of key state actors, law enforcement agencies as well as their own association (GJA) concerning their safety were unsatisfactory. The study recommends that the government ensures the security and safety of journalists and media organizations. Media organizations must ensure a safe and toxic-free work environment through codes of practice, policies, and enforcement; and journalists become familiar with the various types of safety breaches and corrective measures that can be taken.